NARRATIVES OF AFFECTION IN FIVE FEET APARTWRITTEN BY RACHEL LIPPINCOTT, TOBIAS IACONIS, AND MIKKI DAUGHTRY - Mutmainah, Siti Faudziana; Priyawan, Pepen; Sariyati, Ice (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
Five Feet Apart is a romance novel written by Rachel Lippincott, Tobias Iaconis, and Mikki Daughtry about the love of two teenagers who are unable to be close to each other due to illness. This study aims to describe and explain the various types of love language and figurative love language found in the novel Five Feet Apart. This research is based on library resources. This research takes a qualitative approach. The issue in this study is the novel Five Feet Apart's various types of love languages and figurative language of love language. This investigation is divided into three stages. The first step is to gather information. Reading notes is the technique employed. Data analysis is the stage that comes after data collection. The data is analyzed descriptively. The results of the data analysis are then presented in the form of a presentation that includes an explanation of the novel Five Feet Apart. The theoretical triangulation validation method was used, which included document reading, recording, and analysis stages. According to the findings of this study, the expressions in the novel Five Feet Apart use a variety of love languages, including words of affirmation, quality time, physical touch, receiving gifts, and acts of service. Furthermore, in the novel Five Feet Apart, hyperbole, metaphor, simile, and personification are examples of figurative language of love language.Â